Occurrence of Poekilloptera phalaenoides (Hemiptera: Flatidae) on Acacia podalyriaefolia (Mimosoideae) in Viçosa, Minas Gerais, Brazil - MARTINS-PIRES, EVALDO; MOREIRA DA SILVA, ISABEL; PEREIRA, ADRIANO ELIAS; COLA-ZANUNCIO, JOSÉ (Revista Colombiana de Entomología, 2011)
Adults and nymphs of Poekilloptera phalaenoides (Auchenorrhyncha: Flatidae) were found on Acacia podalyriaefolia (Leguminosae: Mimosoideae) in Viçosa, Minas Gerais, in October 2007. This is the first record of this insect in the municipality of Viçosa and on plants of A. podalyriaefolia on which it can complete its full life cycle.